Enzymatic study of the deterioration of melanoxylon brauna seeds aged naturally and artificially - Corte, Viviana Borges; e Borges, Eduardo Euclydes de Limae E.; Leite, Hélio Garcia; Pereira, Bàrbara Luísa Corradi; Gonçalves, José Francisco de Carvalho (Revista Brasileira de Sementes, 2010)
There is no specific knowledge of forest tree seeds regarding the metabolic processes involved during storage which makes the establishment of techniques for their suitable conservation difficult. The object of the present research was to study the role of oxidative stress enzymes and fat metabolism during storage and artificial ageing. Seeds of Melanoxylon brauna - Leguminosae- Caesalpinodeae (brauna) were naturally aged during storage for 0, 3, 6, 9 and 12 months in a cold chamber, and artificially aged (accelerated ageing) during 0, 24, 48, 72 and 96 hours, in order to evaluate the changes in the activity of the enzymes superoxide dismutase and catalase and also the oil content. Germination tests were made and the enzymatic activity and quantification of fat content were measured in the embryonary axis and cotyledons. The natural and accelerated ageing affected the behavior of the seeds in a similar manner causing a reduction in vigour. Although the artificial and natural ageing of the seeds affected the germination in a similar way, the accelerated ageing at 45 °C for 72 hours adequately simulated the enzymatic behavior as demonstrated by the seeds stored for 12 months in the cold chamber. There was a similar gradual reduction in the fat reserves in both ageing systems but without any correlation between natural storage and accelerated ageing.
Estudo enzimático da deterioração de sementes de melanoxylon brauna submetidas ao envelhecimento natural e acelerado
Keywords: Fabaceae; Melanoxylon Brauna